Mistborn : the final empire - Sanderson, Brandon (Sanderson, Brandon. Mistborn, 2014)
Experiencing an epiphany within the most daunting prison of the monstrous Lord Ruler, half-Skaa Kelsier finds himself taking on the powers of a Mistborn, and teams up with ragged orphan Vin in a desperate plot to save their world.